2008
DOI: 10.1182/blood.v112.11.3818.3818
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected Pulmonary Emboli Identified on Routine Cancer Staging MDCT Scans: Impact on Cancer Survival

Abstract: Background: While symptomatic venous thromboemboli (VTE) clearly have an adverse impact on survival among cancer patients, the outcome of cancer patients with unsuspected pulmonary emboli (PE) found on routine cancer staging multi-row detector CT (MDCT) scans is unknown. In order to evaluate survival among cancer patients with unsuspected PE, we expanded on a previous study (O’Connell, JCO2006; 24:4928) of such patients. Methods: We performed a retrospective chart review of cancer patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Symptomatic VTE predicts poorer prognosis in patients with cancer [7]. In a recent retrospective study, survival rates of cancer patients with an unsuspected, asymptomatic PE found on a routine cancer staging CT scan were found to be lower than in matched patients without an asymptomatic PE [8]. Thus, an asymptomatic VTE in cancer patients found during staging of the disease may be an important prognostic marker that might influence management strategies.…”
Section: Baseline Characteristics Of Included Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptomatic VTE predicts poorer prognosis in patients with cancer [7]. In a recent retrospective study, survival rates of cancer patients with an unsuspected, asymptomatic PE found on a routine cancer staging CT scan were found to be lower than in matched patients without an asymptomatic PE [8]. Thus, an asymptomatic VTE in cancer patients found during staging of the disease may be an important prognostic marker that might influence management strategies.…”
Section: Baseline Characteristics Of Included Patientsmentioning
confidence: 99%
“…A small group of studies have provided data on the natural history of patients with an incidental PE [1–8,8–13], but only one provided information on mortality rates. In the study by O’Connel et al.…”
Section: Baseline Characteristics Of Included Patientsmentioning
confidence: 99%
See 1 more Smart Citation